2000
DOI: 10.1128/cmr.13.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Hepatitis C Virus Genotypes

Abstract: SUMMARY On the basis of phylogenetic analysis of nucleotide sequences, multiple genotypes and subtypes of hepatitis C virus (HCV) have been identified. Characterization of these genetic groups is likely to facilitate and contribute to the development of an effective vaccine against infection with HCV. Differences among HCV genotypes in geographic distributions have provided investigators with an epidemiologic marker that can be used to trace the source of HCV infection in a given population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
172
0
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(183 citation statements)
references
References 134 publications
4
172
0
7
Order By: Relevance
“…Genotype 6 has only been found in Southeast Asia. Initially, genotype 5 was thought to be confined to South Africa (1,2), where it has been observed in up to 30% of HCV infections (3). Recent reports have shown that in fact genotype 5 has a worldwide distribution but, except in South Africa, is always a minor component of the HCV population.…”
mentioning
confidence: 99%
“…Genotype 6 has only been found in Southeast Asia. Initially, genotype 5 was thought to be confined to South Africa (1,2), where it has been observed in up to 30% of HCV infections (3). Recent reports have shown that in fact genotype 5 has a worldwide distribution but, except in South Africa, is always a minor component of the HCV population.…”
mentioning
confidence: 99%
“…For instance, genotype 4 is found mainly in the Middle East and North Africa, genotype 5 in southern and central Africa, and genotype 6 in Asia. Although HCV subtypes 2a and 2b are relatively common in North America, Europe, and Japan, subtype 2c has been reported as prevailing in northern Italy [2,3]. In central and northern Europe, genotype 2 has a low prevalence (2%-7%), whereas frequency of genotype 3 amounts to 17%.…”
Section: Epidemiologic Aspectsmentioning
confidence: 99%
“…Comparison of the nucleotide sequence of variants recovered from infected individuals in different risk groups and from different geographic regions has revealed the existence of several genetic groups, called genotypes. Based on differences in HCV RNA sequence, six major genotypes and approximately 100 HCV subtypes have been classified [2][3][4]. Although the natural history of the disease seems to be independent of this viral genetic heterogeneity, genotypes do correlate with the treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…Genotype 3a is most common among American and European intravenous drug users. Genotype 4 tends to be most common in North Africa and the Middle East, while genotypes 5 and 6 are confined to mainly South Africa and Southeast Asia respectively [37]. HCV genotyping is the most predictive parameter used in defining antiviral therapy response rate.…”
Section: Genotypementioning
confidence: 99%